Perceptions of professional nurses regarding the National Core Standards tool in tertiary hospitals in KwaZulu-Natal - Winnie T. Maphumulo; Busisiwe R. Bhengu (AOSIS, 2020)
Background: Internationally, healthcare providers share a common goal of providing safe and high-quality care to every patient. In South Africa, the National Core Standards (NCS) tool was introduced to improve the quality of healthcare delivery. Objectives: This article is aimed to determine the perceptions of nurses concerning the use of NCS as a tool to measure quality care delivery in tertiary hospitals in KwaZulu-Natal. Method: This was a cross-sectional descriptive survey, where a purposive sampling technique was used to select hospitals. Six strata of departments were selected using simple stratified sampling. In each stratum, every second ward was selected from the provided list of wards using a systematic random sampling. The population of professional nurses in selected departments was 3050, from which 437 participants were selected by systematic random sampling. The collected data were analysed using Statistical Package for the Social Sciences (SPSS®) version 25. Results: The study indicated that 53.5% respondents believed that the NCS tool allows them to identify areas of weakness, pointing to risks in basic human rights. However, only 49.7% respondents believed that the NCS tool allows staff inputs to identify relevant innovations. The study recommends improvement in the organisational climate and adoption of strategies that add value to patient care. Conclusion: Professional nurses perceived the NCS tool as a good tool for improving quality of healthcare delivery, but there is a need to improve environmental practice and involvement of all healthcare establishments to increase its effectiveness